EFFECTS OF MEGA DOSE VITAMIN C IN CRITICALLY ILL COVID-19 PATIENTS: A RANDOMIZED CONTROL TRIAL - RANA , MA; IQBAL , J; CHAUDHRY , KA; HAFEEZ , MM; JAVED , M; IQBAL , W; HASHMI , MS; PERVAIZ , R; SIDDIQUI , MH; AWAD , AHA (Biological and Clinical Sciences Research Journal, 2023)
Severe acute respiratory coronavirus 2 (SARS-CoV-2), COVID-19, caused a pandemic that took millions of lives worldwide. The main reason is a lack of preparedness and knowledge about the treatment options. With the advancement in the understanding of the SARS-CoV-2 virus, many treatment options have been analyzed that helped effectively to decrease the mortality caused by this virus. Vitamin C is known to boost immunity and slow down the progression of viral infection. The current study was designed to assess the effectiveness of a high dose of intravenous (IV) vitamin C in COVID-19 infection. The clinical trial registered on 23/12/2020 at ClinicalTrials.gov (NCT04682574) was conducted in Bahria Town International Hospital, Lahore (BTIHL), Fatima Memorial Hospital, Lahore (FMH), and Evercare Hospital Lahore from 28/12/2020 to 10/4/2022. Two hundred seventy-eight critically ill patients with COVID-19 were categorized into two groups. One hundred thirty-nine patients were randomized in group VC (vitamin C), which was given a high dose (30 grams) of intravenous (IV) vitamin C for four days, whereas distilled water as a placebo was given to the control group (n=139) along with standard treatment protocols. All the patients were analyzed for primary outcomes in partial pressure of arterial oxygen (PaO2) to Fraction inspired oxygen (P/F) ratio and survival analysis. At the same time, levels of inflammatory and biochemical markers needed for intubation and length of hospital stay in both groups were compared as the study’s secondary endpoint. Among the two groups, we did not find any differences in 28-day mortality (Log Rank P= 0.11). Similarly, no difference in the P/F ratio on the fourth day after the start of IV vitamin C treatment was noted (p=0.24). The median values of biochemical and inflammatory variables improved significantly in group VC on day 4. However, only hemoglobin levels remained non-significant between the groups. Mean days of hospital stay were slightly longer in group C. However, no statistical significance (p=0.941) was found. Although Group VC needed fewer intubations than Group C, results remained statistically insignificant (p= 0.273). This trial did not find any mortality benefit or improvement of the P/F ratio in critically ill patients. However, the VC group showed improvement in biochemical variables of prognostic importance, which seems to lower the chance of intubation and LOS in group VC. A further clinical trial with a large sample size is needed to reach the final conclusion.